Clients’ experiences of receiving service navigation for mental health support in primary care: findings from a mixed-methods evaluation - Megan Rattray; Tania Shelby-James (BMC Health Services Research)
Abstract Background The ‘Service Navigation Measure’ (SNM) initiative was introduced in 2020 as part of Commonwealth Psychosocial supports delivered through the Primary Health Networks (PHNs) in Australia. The aim of this study was to explore the experiences of clients who received this initiative. Methods An exploratory sequential mixed method study was undertaken in the Australian primary care setting. Quantitative data, which involved closed-ended questions, were collected via a survey. Qualitative data were then collected through open-ended questions in the survey and during one-on-one, semi-structured interviews. This data was collected from clients (consumers, families, carers, and health practitioners) who accessed the service one or more times for mental health support. Interviews were audio recorded and transcribed verbatim. Methodological triangulation was employed to enhance the validity and credibility of the findings. This involved thematically analysing the qualitative data to identify emergent themes and sub-themes, and aligning the quantitative data, which were summarised using frequency (%), to these findings where appropriate. Results A total of 349 clients (159 consumers, 43 family members, 70 carers or support workers, 72 health practitioners, 7 unknown) completed the survey and 8 of these participated in a follow-up interview (7 consumers and 1 health practitioner). Three overarching themes emerged from the data: (i) Receiving helpful and timely support, (ii) Appreciating empathetic and understanding support, and (iii) Valuing and enhancing follow-up support. Conclusions Clients expressed overwhelmingly positive experiences, attributing their satisfaction to timely, helpful, and empathetic support, as well as the vital role of follow-up care. This appreciation extended not only to individuals facing mental health challenges but also to the carers and healthcare practitioners seeking information for those under their care. By incorporating these insights into service navigation practices, healthcare systems may enhance their ability to address the mental health needs of their communities, potentially contributing to improved experiences and outcomes for individuals facing mental health challenges.